THE EFFECTIVENESS OF DST TO DEVELOP SPEAKING ABILITY FOR ENGLISH CLUB STUDENTS - Wulandari, Septiana; Sada, Clarry; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: The purpose of this research is to investigate the effectiveness of using Digital Storytelling (DST) to develop student’s ability in speaking for English Club students of SMK-SMTI Pontianak in academic year 2014/2015. The method used in this research is pre-experimental study that administers pre-test and post-test to measure the effectiveness of the treatment. The sample of this research was 8 members of English Club. The researcher used the measurement technique to collect the data and the tool of data collecting was oral performance tests. The researcher used the t-table α (0.05) and the result of the t-test is 5. The t-table with degree of freedom of 7 is 2.365. The result of computation of t-test in this research is higher than t-table. It proves that the use of Digital Storytelling is strongly effective to develop student’s ability in speaking. Key Words: Digital Storytelling (DST), Speaking Ability Abstrak: Penelitian ini bertujuan untuk mengetahui tingkat keefektifan pengunaan Digital Storytelling untuk mengembangkan kemampuan siswa dalam berbicara bagi siswa English Club di SMK-SMTI Pontianak tahun ajaran 2014/2015. Metode yang digunakan pada penelitian ini yaitu pre-eksperimental dengan melaksanakan pre-test dan post-test untuk mengukur keefektifan treatment. Sampel dalam penelitian ini adalah delapan siswa English Club. Peneliti menggunakan teknik pengukuran untuk mengumpulkan data dan alat yang digunakan untuk mengumpulkan data dengan tes penampilan berbicara. Peneliti menggunakan t-table α (0.05) dan hasil dari t-test adalah 5. T-table dengan derajat kebebasan 7 adalah 2.365. Perhitungan akhir menunjukkan bahwa t-test pada penelitian ini lebih besar dari t-table. Hal tersebut membuktikan bahwa penggunaan Digital Storytelling sangat efektif untuk mengembangkan kemampuan siswa dalam berbicara. Kata kunci: Digital Storytelling (DST), Kemampuan Berbicara